Immunofluorescent characterization of meiotic recombination in human males with variable spermatogenesis. (29th November 2012) - de, M.; Ramos, L.; de, P.
Summary Homologous recombination is the key to meiotic functioning. The basis of this process is provided by numerous SPO11‐induced DNA double‐strand breaks. Repair of these breaks occurs via the crossover (CO) and non‐crossover (NCO) pathways. By means of immunofluorescence staining of Replication protein A (RPA) and MutL homolog 1 (MLH1) in combination with the DNA damage marker γH2AX, we studied transitional (CO and NCO) and late (CO) recombination nodules, respectively. Testicular samples were from non‐obstructive azoospermic probands (testicular spermatozoa were found) and probands that had a history of normal fertility prior to a vasectomy. All probands were ICSI candidates. γH2AX foci mostly colocalized with delayed transitional nodules (RPA) for which variation was found among probands. Highest incidences of colocalization were found in patients. The level of MLH1 signal intensity was lower in probands who showed more frequent γH2AX RPA colocalization in late pachytene, suggesting communication between the CO and NCO pathways. Our results suggest the presence of a genetic risk pathway for children conceived from non‐obstructive azoospermic probands and urge for follow‐up studies investigating the level of recombination involved de novo mutations in these children.